(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2003)
In September 2002, we met with Tomás to talk about his new novel. We decided to do it formally; that’s how we met in his office at Rutgers University. There, amidst photographs of his children and favorite authors, we began to review and talk about his new novel. (Interview)